Extensor-tendons reconstruction using autogenous palmaris longus tendon grafting for rheumatoid arthritis patients - Chen Jung-Kuei; Hung Sheng-Tsai; Hou Yao-Tung; Lee Hung-Maan; Chu Po-Jung; Shih Jui-Tien (Journal of Orthopaedic Surgery and Research, 2008)
Abstract Background The purpose of the study is to retrospectively review the clinical outcome of our study population of middle-aged RA patients who had suffered extensor-tendon rupture. We reported the outcome of autogenous palmaris tendon grafting of multiple extensor tendons at wrist level in 14 middle-aged rheumatoid patients. Methods Between Feb. 2000 to Feb. 2004, thirty-six ruptured wrist level extensor tendons were reconstructed in fourteen rheumatoid patients (11 women and three men) using autogenous palmaris longus tendon as a free interposition graft. In each case, the evaluation was based on both subjective and objective criteria, including the range of MCP joint flexion after surgery, the extension lag at the metacarpophalangeal joint before and after surgery, and the ability of the patient to work. Results and Discussion The average of follow-up was 54.1 months (range, 40 to 72 months). The average range of MCP joint flexion after reconstruction was 66°. The extension lag at the metacarpophalangeal joint significantly improved from a preoperative mean of 38° (range, 25°–60°) to a postoperative mean of 16° (range, 0°–30°). Subjectively all patients were satisfied with the clinical results, and achieved a return to their level of ability before tendon rupture. We found good functional results in our series of interposition grafting using palmaris longus to reconstruct extensor tendon defects in the rheumatoid patients. Conclusion Reconstruction for multiple tendon ruptures is a salvage procedure that is often associated with extensor lag and impairment of overall function. Early aggressive treatment of extensor tendon reconstruction using autogenous palmaris longus tendon as a free interposition graft in the rheumatoid wrist is another viable option to achieve good clinical functional result.